Fullerene alloy formation and the benefits for efficient printing of ternary blend organic solar cells1. Issue 21 (7th June 2015) - Angmo, Dechan; Bjerring, Morten; Nielsen, Niels Chr.; Thompson, Barry C.; Krebs, Frederik C.
<x xml:space="preserve">Abstract</x> CPMAS NMR confirms blends of PCBM and ICBA form alloy in ternary mixtures with P3HT leading to pseudo-binary phase behavior.